Understanding Bilateral FDI Flows in Developing Asia - Hattari, Rabin; Rajan, Ramkishen S. (2012)
Unlike trade flows, there has been little to no detailed examination of foreign direct investment (FDI) flows between Asian economies. This paper uses bilateral FDI flows data to investigate trends in intra-Asian FDI flows over the period 1990-2005. It employs an augmented gravity model to identify the main determinants of intra-Asian FDI flows. Possible drivers of FDI flows, including transactional and informational distance (proxied by distance), real sector variables, financial variables, and quality of institutions are examined.